STRUCTURIZATION OF SPHERES OF THE USE OF EDUCATIONAL SOFTWARE FOR A BRANCH SYSTEM OF VOLUNTARILY CERTIFICATION - Skrypka, K.I.; Sukhikh, А.С. (Journal of Information Technologies in Education (ITE), 2011)
In the article the questions of the use of informative-communication technologies and application of educational software from point of estimation of quality of program products which are used in the field of education are highlighted. In this publication is substantiated that in the conditions of informatization it is necessary to use educational software in parallel with the traditional methods of education, which will realize the complex of methodical purposes. For creation of the normative documents of process of certification of educational software an important task is the structurization of spheres of the mentioned above software usage and description of software tools which provide development of educational software for definite methodical setting.